1991
DOI: 10.5014/ajot.45.7.621
|View full text |Cite
|
Sign up to set email alerts
|

Private Practice Occupational Therapy in the Skilled Nursing Facility: Creative Alliance or Mutual Exploitation?

Abstract: Occupational therapy private practice appears to play a major role in the provision of rehabilitation services in skilled nursing facilities. A critical look at the meaning of private practice, however, indicates that many of today's private practitioners lack characteristics traditionally associated with that term. Group private practices are well suited to retain the essential qualities of private practice while competing effectively in a corporate environment. They accomplish this difficult task by applying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Cossar (1992, p. 160) has suggested that in ‘several respects, trends amongst occupational therapists in private practice are pre‐empting trends in the occupational therapy profession in general’. Although there are published reports about occupational therapy private practitioners from North America and the United Kingdom (Bridle & Hawkes, 1990; Cossar; Faust & Meaker, 1991), there are no Australian studies. Previous studies of private practitioners have involved quantitative methodology with a broad focus on demographic and descriptive data (Bridle & Hawkes; Cossar; McClain et al .).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cossar (1992, p. 160) has suggested that in ‘several respects, trends amongst occupational therapists in private practice are pre‐empting trends in the occupational therapy profession in general’. Although there are published reports about occupational therapy private practitioners from North America and the United Kingdom (Bridle & Hawkes, 1990; Cossar; Faust & Meaker, 1991), there are no Australian studies. Previous studies of private practitioners have involved quantitative methodology with a broad focus on demographic and descriptive data (Bridle & Hawkes; Cossar; McClain et al .).…”
Section: Introductionmentioning
confidence: 99%
“…For the purposes of the current study, a private practitioner in occupational therapy was defined as self‐employed with the ability to function in an autonomous manner as an independent business person meeting his or her individual tax responsibilities for reimbursement income (Bridle & Hawkes, 1990; Faust & Meaker, 1991; Shriver, 1985). Although a private practitioner as defined here may contract to the private or public sector, a private practitioner is not simply defined as a contractor to the private sector or an employee in the private sector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation